Membangun Kesadaran Pelestarian Air : Kontradiksi Ajaran Hindu dengan Perilaku Pencemaran Air di Bali (Kajian Teo-Ekologi): Kontradiksi Ajaran Hindu dengan Perilaku Pencemaran Air di Bali (Kajian Teo-Ekologi) - Adisastra, I Nyoman Surpa; Prabawa, Bagus Ade Tegar (Sphatika: Jurnal Teologi, 2024)
Water is an important subject in Hinduism, including in Bali. The Bhagawad Gītā, Mānava Dharmaśāstra, and a number of manuscripts in Bali teach water conservation. However, there is currently water pollution in lakes, rivers, and the sea. This is a cause for concern, because Bali has been famous for its natural beauty and sustainability. The main cause of pollution is human activity, such as garbage and waste disposal, which affects water quality. This is contrary to Hinduism, which teaches the preservation of nature, including water. Before the pollution gets worse, it is necessary to build awareness of water conservation. The government and traditional villages have issued various regulations. This needs to be implemented by the community for the sustainability of the environment, especially the quality and quantity of water in Bali. The method used in this paper is qualitative with literature review. Several research results on water in Bali were collected and then analyzed. The author also took information from mass media and books. The results  from this article reveal that the reality of pollution in several lakes in Bali contradicts Hindu teachings, which emphasize the importance of water conservation. This scientific article is expected to inspire all interested parties to jointly preserve water for nature and human life.